Breaking up sedentary time with seated upper body activity can regulate metabolic health in obese high‐risk adults: A randomized crossover trial. Issue 12 (20th July 2017) - McCarthy, Matthew; Edwardson, Charlotte L.; Davies, Melanie J.; Henson, Joseph; Rowlands, Alex; King, James A.; Bodicoat, Danielle H.; Khunti, Kamlesh; Yates, Thomas
Abstract : Aims: To investigate the impact of performing short bouts of seated upper body activity on postprandial blood glucose and insulin levels during prolonged sitting. Methods: Participants undertook two 7.5‐hour experimental conditions in randomized order: (1) prolonged sitting only and (2) sitting, interspersed with 5 minutes of seated arm ergometry every 30 minutes. Blood samples were obtained while fasting and throughout the postprandial period after ingestion of two standardized meals. The incremental area under the curve (iAUC) was calculated for glucose and insulin throughout each experimental condition. A paired samples t ‐test was used to assess the difference in iAUC data between conditions for glucose (primary outcome) and insulin (secondary outcome). Results: Thirteen obese adults (7 women, 6 men; mean ± standard deviation [s.d.] age: 66 ± 6 years; body mass index 33.8 ± 3.8 kg/m 2 ) completed this investigation. Compared with the prolonged sitting‐only condition, the implementation of seated arm ergometry every 30 minutes significantly reduced mean blood glucose iAUC (from 7.4 mmol/L/h [95% confidence interval CI 5.2, 9.5] to 3.1 mmol/L/h [95% CI 1.3, 5.0]; P = .001). Significant reductions in mean insulin iAUC (from 696 mU/L/h [95% CI 359, 1032] to 554 mU/L/h [95% CI 298, 811]; P = .047) were also observed. Conclusion: Performing short bouts of arm ergometry during prolonged sitting attenuated postprandial glycaemia despite maintaining a seated posture. This may have clinical significance for those with weight‐bearing difficulty who may struggle with postural change.